Synthesis and Characterization of 2D Metal-Organic Frameworks for Adsorption of Carbon Dioxide and Hydrogen - Tshuma, Piwai; Makhubela, Banothile C. E.; Ndamyabera, Christophe A.; Bourne, Susan A.; Mehlana, Gift (Frontiers in Chemistry, 2020)
The reaction of Cd(NO3)2·4H2O and Zn(NO3)2·6H2O with the bipyridyl dicarboxylate ligand H2bpydc (2,2′-bipyridine-4,4′-dicarboxylic acid) afforded two porous metal organic frameworks [Cd(bpydc)2(DMF)2·2DMF]n (JMS-3) and [Zn(bpydc)(DMF)·DMF]n (JMS-4). X-ray diffraction studies revealed that both JMS-3 and JMS-4 crystallize in the monoclinic crystal. The MOFs possess 2D interdigited networks with (sql) topology. Sorption studies showed that the activated phase of JMS-3 had CO2 volumetric uptakes of 26.50 and 30.89 cm3 (STP) g−1 (1.18 and 1.39 mmol g−1) whist JMS-4 gave 10.96 and 16.08 cm3 (STP) g−1 (0.49 and 0.71 mmol g−1) at 298 and 273 K respectively.